PENGARUH KOMPETENSI DAN DESAIN KERJA TERHADAP KINERJA KARYAWAN ( STUDI KASUS DI DEPARTEMEN GIGI DAN MULUT RSUP DR. MOHAMMAD HOESIN PALEMBANG ) - PURWANDITO PUJORAHARJO; ZUNAIDAH .; YULIANSYAH M.DIAH (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this study was to determine the effect of competence and job design partially or simultaneously and which variables are more dominant effect on the performance of employees of the Dentistry Department of RSUP Dr. Mohammad Hoesin Palembang. This study used a survey method with descriptive approach. Subjects in this study were all employees of the Dentistry Department of RSUP Dr. Mohammad Hoesin Palembang as many as 36 people. The results showed that the competence (X1) and job design (X2) partially (t-test) have a positive influence on employee performance (Y) Dentistry Department of RSUP Dr. Mohammad Hoesin Palembang. This is indicated by the value of each thitung > ttable and probability value < level of significance. Simultaneous test results (F test) showed that the competence and job design simultaneously positive effect on the performance of employees of the Dentistry Department of RSUP Dr. Mohammad Hoesin Palembang with R value of 0.924, which means very strong. The independent variable which gives a more dominant effect on performance, namely competence (X1). This shows that the better their competence will better the performance of the resulting employee Dentistry Department of RSUP Dr. Mohammad Hoesin Palembang.